Estandarización de los procesos de cosecha, postcosecha y transporte del cultivo de Mora de acuerdo con los requerimientos de mercados nacionales e internacionales en el sector Guantuc Cruz, cantón Guaranda, provincia Bolívar, año 2024 - Fernandez Jimenez, Marcia Lorena (2024)
The standardization of harvesting, post-harvest and transportation processes of the blackberry crop in the Guantuc Cruz sector, Guaranda Canton, Bolivar Province, during the period 2024, is an essential initiative to meet the requirements of national and international markets. This project seeks to improve the quality, efficiency and competitiveness of blackberry production in this sector. In this sense, the standardization of harvesting processes involves the implementation of uniform practices aimed at selecting fruit at its optimum point of maturity, thus ensuring consistent quality. In addition, the post-harvest stage focuses on the handling and processing of blackberries in order to maintain their quality during storage and transport. Processes are established for cleaning, grading and packaging of the products, as well as an adequate refrigeration and storage system to prolong the shelf life of the blackberries. The research revealed that transportation plays a key role in the supply chain, so they establish standardized processes for packing, stowage and marketing of blackberry, ensuring the integrity of the product and its arrival at the markets in optimal conditions. This includes the selection of efficient routes and the use of appropriate containers and vehicles, together with cold chain management to maintain product quality. The ultimate goal of this project is to guide compliance with quality and food safety requirements in both domestic and international markets.